Rapid and sensitive sandwich enzyme-linked immunosorbent assay for detection of staphylococcal enterotoxin B in cheese. - Morissette, C (1991)
A rapid and sensitive screening sandwich enzyme-linked immunosorbent assay (ELISA) was developed for the detection of staphylococcal enterotoxin B (SEB) in cheese by using a highly avid anti-SEB antibody (Ab) as the capture Ab (CAb) and as the biotinylated Ab conjugate. The glutaraldehyde fixation method for the immobilization of CAb on polystyrene dipsticks was superior to the adsorption fixation and the adsorption-glutaraldehyde fixation methods. The glutaraldehyde fixation method resulted in a higher surface-saturating CAb concentration as evaluated by the peroxidase saturation technique and by the ability of the CAb-coated dipstick to discriminate between positive and negative controls (index of discrimination). Of nine blocking agents used alone or in pairs, lysine-human serum albumin, bovine serum albumin, human serum albumin, and gelatin effectively saturated available sites on the CAb-coated dipsticks without causing interference with the antigen-Ab reactions. The addition of 1% polyethylene glycol to the diluent of the biotinylated anti-SEB Ab conjugate improved the detection of SEB. A concentration of 4% polyethylene glycol allowed a 5-min reaction time for the streptavidin-biotin-horseradish peroxidase conjugate. Cheddar cheese homogenate reduced the sensitivity of the SEB assay; however, the sensitivity was restored when 1.6% (wt/vol) of either a nonionic detergent (Mega-9) or two zwitterionic detergents (Zwittergent 3-10 and 3-12 detergent) was added to the diluent. By using the rapid sandwich ELISA, a minimum of 0.5 to 1.0 ng of SEB per ml was detected within 45 min. The whole procedure for the analysis of the cheddar cheese samples was completed within 1 h.(ABSTRACT TRUNCATED AT 250 WORDS)